2018
DOI: 10.7759/cureus.3441
|View full text |Cite
|
Sign up to set email alerts
|

Post-surgical Gangrene with Pseudomonas luteola Resulting in Limb Amputation: A Case Review

Abstract: Pseudomonas luteola is a rare infective agent with a variable resistance-sensitivity panel. Clinical suspicion and appropriate empiric treatment is necessary for resolution of such infections. We report a case of post-surgical gangrene as a result of Pseudomonas luteola culminating in limb amputation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In our case, the patient had a community acquired urinary tract infection by this bacterium. P. luteola has a variable sensitivity to penicillins, cephalosporins, tetracyclines, and cotrimoxazole and is often sensitive to imipenem, aminoglycosides and fluoroquinolones such as ciprofloxacin [4,8,9]. In our case, P. luteola was sensitive to piperacillin/ tazobactam, ceftazidime, cefepime, aztreonam and imipenem, but resistant to ampicillin, augmentin, cefotaxim, ceftriaxone, tigecycline, cotrimoxazole, amikacin, gentamicin, tobramycin and ciprofloxacin.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…In our case, the patient had a community acquired urinary tract infection by this bacterium. P. luteola has a variable sensitivity to penicillins, cephalosporins, tetracyclines, and cotrimoxazole and is often sensitive to imipenem, aminoglycosides and fluoroquinolones such as ciprofloxacin [4,8,9]. In our case, P. luteola was sensitive to piperacillin/ tazobactam, ceftazidime, cefepime, aztreonam and imipenem, but resistant to ampicillin, augmentin, cefotaxim, ceftriaxone, tigecycline, cotrimoxazole, amikacin, gentamicin, tobramycin and ciprofloxacin.…”
Section: Discussionmentioning
confidence: 60%
“…According to our research on Pub Med from 1980 until November 2020, we found only 19 cases of P. luteola's infection in adults. A summary of main features of these cases is put in Table 1 [1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. This [9,18,19], peritonitis [10,11], biliary tract infection [17], endophtalmitis [20,21] and cutaneous infection [5,7,8,12,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of the present study are similar to those reported by Sugandhi et al ( 21 ). P. aeruginosa is commonly resistant to antibiotics and can cause severe tissue damage for diabetic patients, resulting in sepsis and amputation ( 21 23 ). In the current study, 15% of the patients infected with P. aeruginosa ultimately underwent amputation, and 50% of all the patients who underwent amputation in the study had P. aeruginosa infections.…”
Section: Discussionmentioning
confidence: 99%